Hubungan Bimbingan Belajar UKMPPD dengan Kelulusan UKMPPD Computer Bassed Test Fakultas Kedokteran Universitas Abulyatama Periode Mei 2017 - Meri Lidiawati; Hilda Hilda (Jurnal Dedikasi Pendidikan, 2018)
Competency test of professional doctor program students (UKMPPD) is a test that implemented to select the medical student in order to achieve the competent doctor. Graduation of UKMPPD-CBT on Medical Education Program Medicine Fakulty of Abulyatama is still very low. In this case, half of students decide to follow the guidance of learning to help them to pass the next UKMPPD-CBT. This reaserch to determine the relationship between guidance of learning with the result of UKMPPD computer based test ( CBT) for the first taker. The design of this research was an analytical survey by using cross sectional method with the total population are 105 samples in this research. And used total sampling technique quality with Medical Faculty of Abulyatama University inclusion criteria. Data obtained using questionnaires and statistical tests using Chi-Square. The result of this research is respondens who followed the guidance of learning pass 44 respondens (54,3) and respondens without follow the guidance of  learning pass 6 respondens(25,0%), with p-value 0,022. The conclusions of this research there is relation between guidance of learning with the result of UKMPPD-CBT in priode Mei 2017 in the Medical Faculty of Abulyatama University..